The great British sewing bee : c - Evelegh, Tessa, author (London : Quadrille, 2014)
This new book accompanies the second BBC TWO 8-part TV series of the Great British Sewing Bee presented by Claudia Winkleman and judged by Patrick Grant and May Martin. This is a fabulous follow-up to excite the appetites of Britain's burgeoning sewers who followed the first series of The Great British Sewing Bee, from beginners to experts. At the heart of this new practical sewing book is a fantastic selection of projects, with a core collection of wardrobe essentials, from a pencil skirt to an easy T-shirt top to a wrap dress so that the sewer can build up a capsule wardrobe. The tempting range of projects reflects the breadth of the TV challenges and includes menswear (such as a shirt and trousers), a selection of designs for babies and small children (such as a fur onesie, dungarees and a little dress) and with more retro and glamorous garments (such as a prom dress and a 60s-style coat). The book will also include 5 full-sized pattern sheets with dress sizes ranging from 8-18, in response to feedback from our readers. With a bright fashion-led selection of colours and patterns, inspiring photography, masterclasses from judges May and Patrick, and the emphasis on the creative elements of choosing fabric and trimmings and fitting garments to your own measurements for the perfect finish, this will be the essential purchase for everyone who bought the first book, and all who watch the new series of The Great British Sewing Bee.
Based on a BBC programme ; with 5 full-size pattern sheets.
Includes bibliographical references.
In English text.
Keywords: Dressmaking -- Patterns; Dressmaking -- Technique; Dressmaking